The effect of the Trans-pacific Partnership Agreement (TPPA) on the accounting profession in Malaysia - Amir Hussin, Muhammad Rosni; Othman, Zaleha; Abdul Hamid, Fathilatul Zakimi (2017)
The Trans-Pacific Partnership Agreement (TPPA) is an ambitious 21st century international trade measure.With promises of mega deals, the TPPA gives the impression that it can provide a wide international trade field that will impact the efficiency and growth of economic sectors, such as the trading, manufacturing and services sectors. The public accounting services sector is one of the professional services that might be impacted by the TPPA.However, there are also contrasting views on the benefits and challenges of the TPPA for the local public accounting firms.Given the crucial impact of the TPPA and its many uncertainties, this conceptual paper seeks to provide an initial understanding of the TPPA and its effect on local public accounting firms. Additionally, this paper discusses the preparation and readiness of local accountants in developing their talents to face the challenges of the TPPA.